1983
DOI: 10.1177/00034894830920s403
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentations of Penetrating Foreign Bodies of the Upper Aerodigestive Tract

Abstract: Only a small number of ingested foreign bodies perforate the esophagus and even a smaller fraction migrate extraluminally. Four such penetrating and migrating foreign bodies of the upper aerodigestive tract are presented. Review of the literature revealed 321 cases of penetrating ingested foreign bodies, of which 252 remained intraluminal and 43 were found extraluminally, with the status of the remainder indeterminate. Analysis revealed that an intraluminal penetrating foreign body carried a higher overall mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
79
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 72 publications
2
79
0
Order By: Relevance
“…Otolaryngologists occasionally find that the use of a flexible laryngeal-fiberscope for discovering bones buried in the mucosa of the pharynx-esophagus relatively difficult, and the consequent delay in diagnosis could result in unnecessary complications. Severe complications are often with vascular, such as aortoesophageal fistula, innominate esophageal fistula, subclavian esophageal fistula and carotid rupture (Remsen et al 1983) and are followed by diffuse or A B Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Otolaryngologists occasionally find that the use of a flexible laryngeal-fiberscope for discovering bones buried in the mucosa of the pharynx-esophagus relatively difficult, and the consequent delay in diagnosis could result in unnecessary complications. Severe complications are often with vascular, such as aortoesophageal fistula, innominate esophageal fistula, subclavian esophageal fistula and carotid rupture (Remsen et al 1983) and are followed by diffuse or A B Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…local suppurative processes, such as periesophageal abscess, mediastinitis, retropharyngeal abscess, thyroid abscess (Chen and Peng 2011) and deep neck abscess (Tien et al 2007;Chung et al 2008). Although the largest case series to date (a worldwide review of studies from 1818 to 1983; Remsen et al 1983) indicated that penetrating foreign bodies are associated with an overall mortality rate of 45%, most previous deaths have been attributed to their occurrence during the preantibiotic era. Recently, several studies (Loh et al 2000;Athanassiadi et al 2002;Nadir et al 2011) have shown that the major complication rate of foreign bodies in the esophagus was 1.6-7.3%, and that the mortality rate was 0-0.73%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A foreign body might also penetrate adjacent visceral structures such as the thyroid gland. Finally, these objects can also penetrate the major blood vessels in the neck and precipitate vascular complications such as aortoesophageal and innominate-esophageal fi stulae and carotid rupture [7].…”
Section: Discussionmentioning
confidence: 99%